Back Cover: Spontaneous Stepwise Self‐Assembly of a Polyoxometalate–Organic Hybrid into Catalytically Active One‐Dimensional Anisotropic Structures (Chem. Eur. J. 31/2014). Issue 31 (28th July 2014) - Yin, Panchao; Bayaguud, Aruuhan; Cheng, Peng; Haso, Fadi; Hu, Lang; Wang, Joy; Vezenov, Dmitri; Winans, Randall E.; Hao, Jian; Li, Tao; Wei, Yongge; Liu, Tianbo
<x xml:space="preserve">Abstract</x> An inorganic–organic hybrid surfactant with a hexavanadate cluster as the polar head group underwent stepwise assembly into micelles and finally, a 1D nanobelt structure with the cooperation of hydrophobic, electrostatic, and hydrogen‐bonding interactions; these last interactions are directional and lead to the anisotropic assemblies. The nanobelts are highly efficient heterogeneous catalysts for the oxidation of organic sulfides because most of the hexavanadates are exposed to the surface, showing its potential application in the petroleum industry and in environmentally benign chemistry. For more details see the Full Paper by T. Li, Y. Wei, T. Liu et al. on page 9589 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>